Implementation of a Flipped Classroom for Nuclear Medicine Physician CME. Issue 3 (2018) - Komarraju, Aparna; Bartel, Twyla B.; Dickinson, Lisa A.; Grant, Frederick D.; Yarbrough, Tracy L.
Abstract : Introduction: Increasingly, emerging technologies are expanding instructional possibilities, with new methods being adopted to improve knowledge acquisition and retention. Within medical education, many new techniques have been employed in the undergraduate setting, with less utilization thus far in the continuing medical education (CME) sphere. This paper discusses the use of a new method for CME—the "flipped classroom, " widely used in undergraduate medical education. This method engages learners by providing content before the live ("in class") session that aids in preparation and fosters in-class engagement. Methods: A flipped classroom method was employed using an online image-rich case-based module and quiz prior to a live CME session at a national nuclear medicine meeting. The preparatory material provided a springboard for in-depth discussion at the live session—a case-based activity utilizing audience response technology. Study participants completed a survey regarding their initial experience with this new instructional method. In addition, focus group interviews were conducted with session attendees who had or had not completed the presession material; transcripts were qualitatively analyzed. Results: Quantitative survey data (completed by two-thirds of the session attendees) suggested that the flipped method was highly valuable and met attendee educational objectives. Analysis of focus group data yielded six themes broadly related to two categories—benefits of the flipped method for CME and programmatic considerations for successfully implementing the flipped method in CME. Discussion: Data from this study have proven encouraging and support further investigations around the incorporation of this innovative teaching method into CME for nuclear imaging specialists.